PENDAMPINGAN PEMANFAATAN LIMBAH BONGGOL JAGUNG (JANGGEL) SEBAGAI MEDIA TANAM JAMUR DI DESA DARA KUNCI, SAMBELIA, LOMBOK TIMUR - Astiti, Ida Ayu Made Widya; Jurnal Wicara; Alfhina, Luluk; Meilieana, Eca; Putra, Lalu; Hidayani, Nurul; Adiat, Dina; Abidin, Muhammad; Prayanto, Muhammad; Susilawati, Desi; Ahfal, Syahrul; Rizal Abidin, Muhammad (Universitas Mataram, 2025)
The majority of the residents in Dara Kunci Village rely on the agricultural sector. Maize serves as the primary commodity in alignment with the national food security program. However, only the kernels are utilized, while the cobs remain as agricultural waste. In fact, maize cobs contain substances that can accelerate the growth of mushrooms. Therefore, the Community Service Program (KKN) team from the University of Mataram (UNRAM) initiated a training program on the utilization of maize cobs as mushroom cultivation media, aiming to reduce agricultural waste and develop economically valuable products. Furthermore, it is expected that the people of Dara Kunci Village will be able to implement this mushroom cultivation independently. The applied methodology consisted of two stages, namely surveys and observations, as well as training. The activities were carried out in accordance with the proposed methods. During the training, all stages of mushroom cultivation using maize cobs were explained in detail, including critical aspects that required particular attention. Prior to the training, the team had already cultivated mushrooms as a demonstrative example, proving that this waste utilization is indeed beneficial. In doing so, the team was able to highlight factors that may inhibit mushroom production and provide appropriate solutions to address such issues. Moreover, following the training, several community members successfully cultivated mushrooms within the expected growth period.